The Influence of Customer Relationship Marketing and Service Quality on Customer Satisfaction with Brand Image as a Mediating Variable - Made Agus Adhy Putra; Luh Komang Candra Dewi (Journal of Social Science, 2023)
The banking sector plays a crucial role in a country's economy, with numerous banks in Indonesia providing consumers with various choices for their financial needs. This research aims to analyze: 1) the impact of customer relationship marketing on customer satisfaction, 2) service quality's influence on customer satisfaction mediated by brand image, 3) the link between customer relationship marketing and brand image, 4) the connection between service quality and brand image, 5) brand image's effect on customer satisfaction, 6) customer relationship marketing's indirect impact on customer satisfaction via brand image, and 7) service quality's indirect effect on customer satisfaction through brand image. This quantitative descriptive study involved 80 respondents and used SPSS 24 for analysis. The results revealed that: (1) Customer Relationship Marketing positively influences customer satisfaction, (2) service quality positively affects customer satisfaction through brand image mediation, (3) Customer Relationship Marketing has a positive impact on brand image, (4) service quality positively influences brand image, (5) brand image positively affects customer satisfaction, (6) Customer Relationship Marketing indirectly influences customer satisfaction through brand image mediation, and (7) service quality indirectly impacts customer satisfaction through brand image mediation. All variables in the study demonstrated a positive and significant influence, confirming their validity.